2007
DOI: 10.1063/1.2430629
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Si capping layer suppresses charge trapping in HfOxNy∕Ge metal-insulator-semiconductor capacitors

Abstract: In this study the authors investigated the Ge outdiffusion characteristics of HfO x N y /Ge metal-insulator-semiconductor capacitors to determine their charge trapping behavior. Capping the Ge substrate with an ultrathin Si layer inhibits the incorporation of Ge into the high-k bulk dielectric in the form of GeO x , thereby diminishing the resultant oxide charge trapping. The thermal stability of the entire capacitor structure was also improved after performing an additional Si passivation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Reduction of J g by Si IL is clearly observed (Fig. 3(b)), which is attributed to the improvement of interface quality by blocking the Ge outdiffusion as in [9][10][11]. However, the further J g reduction is not observed any more for the thicker Si IL (Fig.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Reduction of J g by Si IL is clearly observed (Fig. 3(b)), which is attributed to the improvement of interface quality by blocking the Ge outdiffusion as in [9][10][11]. However, the further J g reduction is not observed any more for the thicker Si IL (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…As shown in Fig. 2(b), decrease of CET values after the PMA is due to the densification of high-k dielectric or improvement of interface quality [9].…”
Section: Resultsmentioning
confidence: 97%
“…There have been many reports on various interfacial passivation layers, such as ultrathin Si capping layers on Ge substrates, Ge nitride interfacial layers, , Al 2 O 3 and LaAlO 3 dielectric inter layers, , and high-quality GeO 2 interfacial layers formed by plasma oxidation or high pressure oxidation. , Among the various passivation techniques, a Si capping layer on a Ge substrate has drawn a great deal of attention because of its superior electrical performance. Cheng et al reported that a Si capping layer on a Ge substrate retarded the GeO volatilization and suppressed the C–V hysteresis of the HfO x N y gate dielectric films in the MOS structure . The decrease in the C–V hysteresis by the Si capping layer was explained by the Si–O bonds having larger Gibbs free energies and higher thermodynamic stabilities than the Ge–O bonds, such that the reaction between the oxide and Ge substrate could be efficiently suppressed .…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al reported that a Si capping layer on a Ge substrate retarded the GeO volatilization and suppressed the C–V hysteresis of the HfO x N y gate dielectric films in the MOS structure . The decrease in the C–V hysteresis by the Si capping layer was explained by the Si–O bonds having larger Gibbs free energies and higher thermodynamic stabilities than the Ge–O bonds, such that the reaction between the oxide and Ge substrate could be efficiently suppressed . In most of the previous studies, a Si capping layer was formed on a Ge substrate either by epitaxial growth of several monolayers of Si or by annealing in ambient SiH 4 (or Si 2 H 4 ). However, not many studies of Si-containing passivation layers grown by an atomic layer deposition (ALD) method on Ge substrates have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…3. Previous works 11,12 indicate the possibility of surface deposition of GeO generated in the annealing chamber due to oxidation of the back side of the Ge substrate. In this work, such oxidation would be due to residual oxygen in the furnace.…”
mentioning
confidence: 99%